Os pensamentos jurídicos dos juízes de 1º grau do Estado de Goiás nas questões possessórias agrárias numa avaliação jurimétrica (2010 a 2020) - Lemos Júnior, Marco Antônio de Oliveira (2021)
This dissertation aims to investigate and build a statistical overview of the applicability of the legal dogmatics of possession in the context of agrarian conflicts over land disputes. The investigation will be based on judicial decisions, in possessory actions in rural areas, rendered by 1st degree judges of jurisdiction of the Judiciary Branch of Goiás, between 2010 and 2020. The study aims to reveal, through statistical objectivity, the degree of alignment of Goiás magistrates to the civilist or agrarian dogmatics of possession. Such strands of legal thought are conceptual and dogmatic developments of the possessory phenomenon, having different constitutive elements. Civil possession is based on the existential element 'corpus', considering as possessor anyone who actually has the exer-cise, full or not, of any of the powers inherent to property. In contrast, agrarian possession is characterized by the work of the land carried out by the owner himself, for the production of a typically agrarian activity, with effective culture and habitual housing for him and his family. While civil possession is subordinate to the legal concept of property, agrarian pos-session is autonomous to it, as it is evidenced by the functionalization of the land by the direct owner and not always by the property title. The act of working the land ends up radi-ating benefits to society and dignity to the owner. It is a matter of implementing the principles of the social function of the land and the dignity of the human person. Thus, in the face of an agrarian possessory action, how did the 1st degree judges of Goiás jurisdiction manifest in their decisions their alignment with the legal dogmatics of possession? Was there any predominance in the applicability of a civilist or jusagrarist dogmatic linked to possession? Before answering these problematizations, this research will carry out a historical, legal and doctrinal explanation about the possessory phenomenon. Therefore, the classical and so-ciological theories of ownership will be addressed. Especially regarding this last theory of possession, it will be discussed about the notion of the social function of possession as a precursor of the principle of human dignity and characterizing agrarian possession. Subse-quently, the delimiting concepts of the scientific research method, specific to the area of Law, called Jurimetry, which will be used in this dissertation, will be worked on. Afterwards, the processes of obtaining and formalizing the data will be detailed, which will be statistically calculated by the jurimetric method, based on the court decisions. The results found will be disserted with the aid of graphics, through descriptive statistics. It will still be possible to measure, through calculations of Bayesian inferential statistics, the predominance, be-tween the civilist or jusagrarian dogmatics of possession, of applicability of the possessory legal positions of the judges of the 1st degree of jurisdiction of the Judiciary Branch of the State of Goiás.